Influence of the dynamics of inclusion on elastic wave propagation in a waveguide - Shubin, Sergey Nikolaevich; Gilyov, Evgeny Evgenievich; Borovkov, Aleksey Ivanivich (Computational Continuum Mechanics, 2011)
The purpose of this study is to determine the geometric sizes of an inclusion in a waveguide through the analysis of acoustic wave passage. The influence of a spectrum of inclusion on reflected and transmitted waves is determined by considering the one-dimensional model of an infinite rod with an inertial and elastic inclusion. The obtained result is generalized to the case of an acoustic waveguide with an absolutely rigid inclusion in the form of a cylinder. The relationship between the geometric sizes of the inclusion and the spectral distribution of reflected and transmitted waves is demonstrated.
Keywords: waveguide; inclusion; spectral distribution; eigenfrequency